(untitled) (Journal of Hama University, 2020)
This study aimed to know the extent of the commitment of the Syrian universities operating in the city of Damascus to the national academic reference standards, in order to develop the applicable work systems in those universities and reach a new style in administrative work that guarantees them excellence and success, and this study was applied to the University of Damascus in addition to (3) Other private universities operating in the city of Damascus, the researcher used the descriptive analytical approach and used the questionnaire tool to collect information, and then conducting the appropriate statistical analysis using the statistical treatment methods included in the program (SPSS24), where the sample members were drawn using the sample method Stratified randomness according to the ratio of the indigenous population to each stratum. The study sample reached (247) workers. The results of the study showed that there are statistically significant differences in the perception of the respondents of the level of adherence of universities to the national academic reference standards due to the variable of administrative dependency and for the benefit of private universities, and the variable of scientific qualification and for the benefit of workers with higher educational qualification, and variable number of years of experience and for workers with more years of experience, Variable and functional level in favor of the higher functional level.